(untitled) - Dobrotkova, Marta; Vrabel, Jan (Doprava a spoje, 2011)
The price, which is offered for piece shipments transport services by company, should have covered the costs for it. One of the most important cost, which affected the level of price, is the cost for fuel. This kind of cost largely depends on the economic situation of the country. For this reason it is suitable to agree in the contract how to reflect change of fuel price in the final price.